2020
DOI: 10.1111/jerd.12638
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength of glass ionomer and resin‐based cements to different types of zirconia

Abstract: Objective: To investigate the shear bond strength (SBS) of a glass ionomer (GI) cement, an 10-methacryloyloxy-decyl dihydrogen phosphate (MDP)-based adhesive resin cement (MDP-based AC), an MDP-based self-adhesive resin cement (MDP-based SAC), an MDP-free self-adhesive resin cement (MDP-free SAC), and a resin-modified GI (RMGI) cement to a 3 mol% yttria-stabilized (3Y-TZP) and a 5 mol% yttria partially stabilized zirconia (5Y-PSZ). Materials and methods: Fifty blocks were produced using 3Y-TZP and 5Y-PSZ, assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…The search revealed 18 studies on bonding to 5Y-TZP zirconia. 86,95,96,[98][99][100][101][102][103][104][105][106][107][108][109][110][111] The three types of surface pretreatment methods were applied: mechanical, through alumina and glass-bead APA; chemical-mechanical, through TBS, lithium disilicate glass-ceramic coat, and plasma treatment; and chemical, through piranha acid etch solution and hot chemical etching (Table 2). Alumina APA particle sizes ranged between 40-110 μm at 1-6 bar pressure.…”
Section: Bonding To 5y-tzpmentioning
confidence: 99%
See 2 more Smart Citations
“…The search revealed 18 studies on bonding to 5Y-TZP zirconia. 86,95,96,[98][99][100][101][102][103][104][105][106][107][108][109][110][111] The three types of surface pretreatment methods were applied: mechanical, through alumina and glass-bead APA; chemical-mechanical, through TBS, lithium disilicate glass-ceramic coat, and plasma treatment; and chemical, through piranha acid etch solution and hot chemical etching (Table 2). Alumina APA particle sizes ranged between 40-110 μm at 1-6 bar pressure.…”
Section: Bonding To 5y-tzpmentioning
confidence: 99%
“…127,128 Outcomes of different types of functional monomer-based primers and resin cements to APA 5Y-TZP are inconsistent (Table 2). De Angelis and coworkers 108 found that MDP monomer-based primers and resin cements performed significantly better than phosphate monomerbased resin cements. Failure modes obtained with a phosphate monomer-based resin cement (RelyX Unicem 2 Clicker, 3 M ESPE, Seefeld, Germany) were mainly adhesive (Table 2).…”
Section: Bonding To 5y-tzpmentioning
confidence: 99%
See 1 more Smart Citation
“…The MDP acts on the hydroxyl groups of the zirconia oxide surface layer, interacting at an interfacial level. Thus, each phosphate group joins on to one or three zirconium atoms, creating phosphate zirconium, which is a more thermally and hydrolytically stable zirconium salt, which may justify the better adhesive behavior of this surface treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, universal adhesives present functional monomers in their composition to promote adhesion to surfaces based on metallic oxides, such as zirconia and other metal alloys. Recent literature showed different and non-standardized aging methods to test the stability of the bonding between 10-MDP and zirconia, which allow a great variability in the obtained results [ 22 , 23 ]. Thus, the aim of this in vitro study was to evaluate the effectiveness of different chemical-based adhesive techniques in promoting bond strength between zirconia and luting cement.…”
Section: Introductionmentioning
confidence: 99%